YTHDC1 Promotes Stemness Maintenance and Malignant Progression in Head and Neck Squamous Cell Carcinoma - Junquan Weng; Haidong Fan; Huijuan Liu; Su Tang; Yuyan Zheng (Stem Cells International)
Background. YTH domain containing 1 (YTHDC1), an N6-methyladenosine (m6A) modification reading protein, plays a key role in regulating RNA translation and degradation. However, the role of YTHDC1 in head and neck squamous cell carcinoma (HNSCC) cancer stem cells remains largely unknown. This study is aimed at investigating the role of YTHDC1 in HNSCC and exploring its role in regulating cancer stem cells. Methods. RNA sequencing was used to detect differentially expressed genes (DEGs) between SCC9 spheres and SCC9 cells and to uncover molecular pathways and target molecules associated with CSCs. We detected YTHDC1 expression in The Cancer Genome Atlas (TCGA) database data and clinical samples. Subsequently, YTHDC1 gene suppression assays were performed in HNSCC cell lines to investigate the effect of YTHDC1 on tumor cell stemness maintenance, proliferation, and migration capacity. To further confirm the role of YTHDC1 in regulating cancer stem cells in HNSCC, we analyzed online HNSCC single-cell transcriptomic data to investigate YTHDC1 expression patterns at the single-cell level and the correlation of these levels with the expression of stem cell markers. Results. YTHDC1 expression levels were significantly upregulated in SCC9 spheres, and YTHDC1 was aberrantly expressed in HNSCC tumor tissues. The increased YTHDC1 expression was closely correlated with the clinical characteristics of HNSCC patients. YTHDC1 regulates the malignant phenotype of HNSCC in both in vivo and in vitro studies. Further single-cell transcriptomic data analysis revealed that YTHDC1 positively correlated with malignant epithelial cell stemness capacity at the single-cell level, and that YTHDC1 was involved in regulating stemness maintenance in HNSCC. Conclusions. These findings suggest that YTHDC1 may serve as a biomarker for stem maintenance and malignant progression in HNSCC, providing new insights into the treatment of cancer.